Review of Nychia marshalli in the Western Palaearctic, with new records and distributional notes (Hemiptera: Heteroptera: Notonectidae) - Cianferoni, Fabio; Pintar, Matthew R. (Zootaxa, 2024)
The backswimmer Nychia marshalli (Scott, 1872) (Hemiptera: Heteroptera: Notonectidae) is reported for the first time from Italy on the island of Sardinia. A new record of N. marshalli from Corsica (the first from the eastern coast) is provided and the distribution of the species in the Western Palearctic region is summarized. Although records of N. marshalli continue to be documented around the western Mediterranean, its distribution in the remaining part of its range can still be improved and the relationship of the Palaearctic population to sub-Saharan populations of Nychia needs to be further investigated.